Perception of Face and Body Expressions Using Electromyography, Pupillometry and Gaze Measures - Kret, Mariska; Stekelenburg, Jeroen; Roelofs, Karin; De Gelder, Beatrice (Frontiers in Psychology, 2013)
Traditional emotion theories stress the importance of the face in the expression of emotions but bodily expressions are becoming increasingly important. Here we tested the hypothesis that similar physiological responses can be evoked by observing emotional face and body signals and that the reaction to angry signals is amplified in anxious individuals. We designed three experiments in which participants categorized emotional expressions from isolated facial and bodily expressions and from emotionally congruent and incongruent face-body compounds. Participants’ fixations were measured and their pupil size recorded with eye-tracking equipment, and their facial reactions measured with electromyography (EMG). The behavioral results support our prediction that the recognition of a facial expression is improved in the context of a matching posture and importantly, also vice versa. From their facial expression, it appeared that observers acted with signs of negative emotionality (increased corrugator activity) to angry and fearful facial expressions and with positive emotionality (increased zygomaticus) to happy facial expressions. What we predicted and found, was that angry and fearful cues from the face or the body, attracted more attention than happy cues. We further observed that responses evoked by angry cues were amplified in individuals with high anxiety scores. In sum, we show that people process bodily expressions of emotion in a similar fashion as facial expressions and that the congruency between the emotional signals from the face and body ameliorates the recognition of the emotion.